FAKTOR-FAKTOR PENYEBAB KEGAGALAN KONTRAKTOR DALAM EVALUASI PENAWARAN DI DAERAH ISTIMEWA YOGYAKARTA - Simalango, Daniel Rashoky; Setiawan, Harijanto (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2019)
Various factors were found as the cause of the contractor's failure in bid evaluation in the tender of government projects. This study aims to explore the factors that cause contractors to fail in electronic project procurement in the Special Region of Yogyakarta. The study was conducted based on a qualitative approach with documents as data sources. The secondary data was obtained from the Electronic Procurement Service Website (LPSE) of the Special Region of Yogyakarta in 2017. Qualitative data analysis was carried out using NVivo software in order to classify data that has similar meanings, which can be considered as the factors that cause failure of contractors in government projects tender. The results show that technical factors are the most common cause of failure, both in building projects, roads and bridges, and waterworks. Specifically, the technical factors that are the cause of the failure are different for each type of project. Technical factors related to core personnel are the cause of failure in building and waterworks projects, while the construction method is the cause of failure in road and bridge projects.